Peran Pengalaman Merek dalam Menciptakan Loyalitas Konsumen dengan Kesesuaian Diri sebagai Mediator: Studi pada Konsumen Merek Kosmetik Emina - Nava Vania Putri Arianto; I Made Bayu Dirgantara (Diponegoro Journal of Management, 2025)
The beauty industry in Indonesia has experienced rapid growth, driven by increasing public awareness of self-care, the dominance of younger age groups, and the advancement of e-commerce and social media. The growing competition has made consumers more selective, thus requiring effective strategies to build brand loyalty. Emina, a local brand targeting the teenage segment, has gained increasing popularity. In fact, Emina has successfully secured the second position in national cosmetic usage. However, the intensifying competition demands that Emina continuously optimize its strategies to build consumer loyalty and maintain its market position. Based on this background, the purpose of this study is to analyze the effect of brand experience on brand loyalty through self-congruity as an intervening variable (a study on Emina consumers). The population in this study consists of Emina consumers in Semarang, with a total sample of 160 respondents. Data were collected through an online questionnaire. The data were analyzed using the Structural Equation Modeling (SEM) method with the help of AMOS 26.0 software. The results of the study show that brand experience has a significant effect on self-congruity, and self-congruity significantly influences brand loyalty. It is found that self-congruity fully mediates the effect of brand experience on brand loyalty. Meanwhile, the direct effect of brand experience on brand loyalty is not significant. This study also finds that self-congruity is the key predictor in influencing consumer brand loyalty.